Diversity and Regionalism in International Commercial Arbitration - Braghetta, Adriana (Victoria University of Wellington Law Review, 2015)
New Zealand Law Foundation International Dispute Resolution Lecture 2015, delivered at Stone Lecture Theatre, Auckland Law School, 19 October 2015. The lecture focuses on diversity and regionalism in international commercial practice, looking specifically at the representation of new players.